Identification of prognostic biomarkers in the CMTM family genes of human ovarian cancer through bioinformatics analysis and experimental verification - Zhang, Mengjun; Wang, Jialin; Yue, Haodi; Zhang, Lindong (Frontiers in Genetics, 2022)
Background: Ovarian cancer (OV) is one of the most common gynecological malignancies worldwide, and its immunotherapy has considerable prospects. Multiple members of the CMTM family were aberrantly expressed in human cancers and controled key malignant biological processes and immune regulation in cancer development. However, little is known about the function of this gene family in ovarian cancer, especially in terms of immunity. Methods: GEPIA, Oncomine, HPA, Kaplan-Meier plotter, cBioPortal, GeneMANIA and TIMER were used to analyze the differential gene expression, prognostic value, genetic alterations and alterations in the immune microenvironment of the CMTM family in patients with ovarian cancer. Importantly, RT-qPCR was used to verify the gene expression of the CMTM family. Results: CMTM1/3/4/6/7/8 showed abnormally high expression at the mRNA and protein levels in OV tissues based on the GEPIA and HPA databases. RT-qPCR showed that CMTM1/6/8 was highly expressed in ovarian cancer cell lines. IHC verified that CMTM8 is highly expressed in ovarian cancer tissues and is closely related to Ki-67.Survival analysis showed that high expression of CMTM1/2/3/5/8 can lead to a significant reduction in overall survival and progression-free survival. There were many types of genetic alterations in the CMTM family. And CMTM1/2/3/6 had a certain correlation with the changes of immune microenvironment such as immune cell infiltration and immune checkpoint expression, which may be the potential mechanism of the CMTM family in ovarian cancer. IHC verified that CMTM6 is highly expressed in ovarian cancer tissues and is closely related to PD-L1. Conclusion: This study confirmed that the CMTM family has abnormal expression in ovarian cancer and CMTM8 can be used as a biomarker for prognostic evaluation. And the CMTM family may be used as a potential target for immunotherapy based on the suppression of immune checkpoints.